ANTIDERM Dermatitis Consultation Application User Interface Design Model Using Design Sprint Method - Liza Trisnawati; Setiawan, Debi; Ryanto, Stephen (JIM - Journal International Multidisciplinary, 2023)
Dermatitis is one of the inflammatory skin diseases that cause a variety of symptoms that can happen to all ages, particularly to children. Because of the many varieties of the dermatitis illness, patients are usually advised to consult with doctors specializing in the disease. However, oftentimes there are difficulties in meeting the doctors for consultation. Therefore, a consultation application is essential to ease communications between doctors and patients, alongside containing several information regarding the symptoms of dermatitis so that the public could learn the symptoms of dermatitis and how to avoid this dangerous disease. The mobile-based application ANTIDERM is one such application built for bequeathing to the public an efficient and accessible service to consult, do an early diagnosis, and look up news regarding the dermatitis disease. The application’s user interface (UI) basis are the five steps of the Design Sprint method that is targeted towards producing an application that can reach the expected target while providing a satisfying user experience. The result is an information system-based application design model that is very intuitive and streamlines the communication cycle between doctors and patients while easing the spread of information regarding the dermatitis disease.